Identification of genes associated with growth cessation and bud dormancy entrance using a dormancy-incapable tree mutant - Reighard Gregory L; Li Zhigang; Jiménez Sergio; Bielenberg Douglas G (BMC Plant Biology, 2010)
Abstract Background In many tree species the perception of short days (SD) can trigger growth cessation, dormancy entrance, and the establishment of a chilling requirement for bud break. The molecular mechanisms connecting photoperiod perception, growth cessation and dormancy entrance in perennials are not clearly understood. The peach [Prunus persica (L.) Batsch] evergrowing (evg) mutant fails to cease growth and therefore cannot enter dormancy under SD. We used the evg mutant to filter gene expression associated with growth cessation after exposure to SD. Wild-type and evg plants were grown under controlled conditions of long days (16 h/8 h) followed by transfer to SD (8 h/16 h) for eight weeks. Apical tissues were sampled at zero, one, two, four, and eight weeks of SD and suppression subtractive hybridization was performed between genotypes at the same time points. Results We identified 23 up-regulated genes in the wild-type with respect to the mutant during SD exposure. We used quantitative real-time PCR to verify the expression of the differentially expressed genes in wild-type tissues following the transition to SD treatment. Three general expression patterns were evident: one group of genes decreased at the time of growth cessation (after 2 weeks in SD), another that increased immediately after the SD exposure and then remained steady, and another that increased throughout SD exposure. Conclusions The use of the dormancy-incapable mutant evg has allowed us to reduce the number of genes typically detected by differential display techniques for SD experiments. These genes are candidates for involvement in the signalling pathway leading from photoperiod perception to growth cessation and dormancy entrance and will be the target of future investigations.